005 Filling in the gaps: precision MRI reporting in multiple sclerosis clinical practice. Issue 6 (24th May 2018) - Beadnall, Heidi; Barnett, Yael; Ly, Linda; Wang, Chenyu; Billiet, Thibo; Ribbens, Annemie; Hecke, Wim Van; Masters, Lynette; Hardy, Todd A; Barnett, Michael H
Abstract : Introduction: Clinical multiple sclerosis (MS) magnetic resonance imaging (MRI) brain reports provide important information to neurologists. The quantitative data reported varies between centres and radiologists. Structured MRI reporting and formal quantitative MRI (QMRI) analysis may assist clinicians with patient management. The objective is to compare quantitative data derived from standard clinical reports, structured neuroradiologist reviews, local QMRI analyses and fully-automated MSmetrix QMRI analyses, in a longitudinal clinical MS cohort. Methods: Clinical brain MRI scans separated by one-year minimum, from the same patient on the same scanner, were evaluated. Quantitative information was extracted from the clinical reports and structured neuroradiologist reviews. MRI scan-pairs were analysed locally by imaging-analysts and centrally by MSmetrix. Results: 50 MS patients, baseline age 39.02 (9.06) years, disease duration 9.11 (6.88) years and Expanded Disability Status Scale score 1.91 (1.62), were included. Compared to clinical reports, structured neuroradiologist reviews provided increased semi-/quantitative data; baseline T2 and T1 lesion burden (50% vs 100%; 2% vs 100%), baseline brain volume-loss (BVL; 72% vs 100%), new T1 lesions (0% vs 100%), regional brain atrophy (BA; 20% vs 100%). Lesion and brain volumes were not provided in radiology reports/reviews. Comparison of local and central QMRI revealed moderate-strong Pearson correlations for most metrics; Intra-class correlations varied more widely. Statistical consistency existed across all methods in detecting new T2 lesions. Radiologist-identified baseline BVL was associated with lower quantitatively-measured brain volumes. Local QMRI longitudinal BA rates >0.4% and >0.8%, were 48% and 26% respectively. Neuroradiologist review identified BA in 12%. Conclusion: Structured neuroradiology review provided additional quantitative information over standard clinical reports. Quantitative data measured using local and MSmetrix pipelines were generally well associated but are not interchangeable. Longitudinal whole brain and regional atrophy is not reliably identified by radiologists and QMRI analysis provides a clear advantage in this regard. Structured reporting, and formal QMRI analysis, provide additional quantitative MRI data that may assist clinical decision-making in MS.